PENGARUH INDUKSI EMOSI TERHADAP KEPUTUSAN MEMBELI PRODUK - Yani Tri Wijayanti; Adib Ahmad (Profetik: Jurnal Komunikasi, 2014)
The aim of this study is to investigate the effects of induced positive and negative emotion on the risky buying product decision making. The authors hypothesize that participant with induced negative emotion was more taking risk when faced with risky buying product contrast with participant induced positive emotion. Participant were 132 people consist of high-school student, undergraduate student, and adult. The results showed that mean differences was not support the hypothese. Arguments of the research result were discussed.